1994
DOI: 10.1093/clinchem/40.5.774
|View full text |Cite
|
Sign up to set email alerts
|

Iron-deficiency anemia is associated with high concentrations of transferrin receptor in serum

Abstract: We evaluated the use of transferrin receptor (TfR) in serum as an index of iron deficiency in 19 patients diagnosed as having iron-deficiency anemia, in 17 patients with anemia of chronic disease, and in a control group of 19 nonanemic patients who underwent elective ocular or nasopharyngeal surgery. The assessment of iron status of the anemic patients was based on the presence of stainable iron on bone marrow examination. In the patients with iron-deficiency anemia, the serum TfR concentration was 5.3 +/- 1.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
49
0
2

Year Published

1999
1999
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(53 citation statements)
references
References 13 publications
0
49
0
2
Order By: Relevance
“…Serum levels of soluble transferrin receptor (sTfR) have been extensively reported to be elevated in iron deficiency (Flowers et al 1989;Kohgo et al 1989;Huebers et al 1990;Punnonen, Irjala & Rajamaki 1994) and to be unaffected by chronic disease (Punnonen et al 1994;Kohgo et al 1988;Ferguson et al 1992). The rationale is that transferrin receptors, which mediate cellular uptake of iron, are expressed in proportion to the cell requirement for iron, and that cell-associated transferrin receptor is subject to proteolysis that generates a soluble form of the receptor (sTfR), which circulates in plasma.…”
Section: Introductionmentioning
confidence: 99%
“…Serum levels of soluble transferrin receptor (sTfR) have been extensively reported to be elevated in iron deficiency (Flowers et al 1989;Kohgo et al 1989;Huebers et al 1990;Punnonen, Irjala & Rajamaki 1994) and to be unaffected by chronic disease (Punnonen et al 1994;Kohgo et al 1988;Ferguson et al 1992). The rationale is that transferrin receptors, which mediate cellular uptake of iron, are expressed in proportion to the cell requirement for iron, and that cell-associated transferrin receptor is subject to proteolysis that generates a soluble form of the receptor (sTfR), which circulates in plasma.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, serum TfR measurement was introduced as a useful indicator of bone marrow erythropoiesis (Kohgo et al, 1987;Muta et al, 1987;Shintani et al, 1994). Recent studies have shown that the measurement of serum TfR is a dependable test for the diagnosis of iron deficiency and is useful for differentiating IDA from the anaemia of chronic disease and inflammation (Skikne et al, 1990;Petterson et al, 1994;Punnonen et al, 1994Punnonen et al, , 1997Gimferrer et al, 1997;North et al, 1997). It may be speculated that, similarly to serum TfR, the number of cells carrying TfR would also be ᭧ 1999 Blackwell Science Ltd Correspondence: Professor Ç igdem Altay, Department of Paediatrics, Ihsan Dogramacı Children's Hospital, Hacettepe University, 06100 Ankara, Turkey.…”
mentioning
confidence: 99%
“…Elevated levels of sTfR were found in the serum of patients with sickle cell anemia (Flowers et al, 1989), b-thalassemia with hemoglobin E or H disease (Huebers & Finch, 1987), hereditary spherocytosis and autoimmune hemolytic anemia (Huebers et al, 1990), but sTfR is mainly used for the differentiation of iron deficiency anemia, accompanied by an increase in the sTfR level, from anemia of chronic disease, which has normal sTfR levels (Ferguson et al, 1992;Punnonen, Irjala & Rajamaki, 1994). sTfR levels can increase threefold to sevenfold in iron deficiency anemia and up to eightfold in b-thalassemia/Hb E disease (Thorstensen & Romslo, 1993).…”
Section: S U M M a R Ymentioning
confidence: 99%